"Мы сеем и сеем...": Вавожский район (1929-1999) / Районный Совет депутатов, Администрация Вавожского района УР - Дзюина К. Н. (Удмуртия, 1999)
Экземпляры: ф. 2 (20160921) / Инвентарный номер: 104708 / Цена: 10.00 / Авт.знак: М 94 / ГРНТИ: 03 / ББК: 63.3(2Рос.Удм)